Using docker to assist Q&A forum users - MELO, Luís Henrique de Souza (2019)
Q&A forums are today an important tool to assist developers in programming tasks. Unfortunately, contributions to these forums are often unclear and incomplete as developers typically adopt a liberal style when writing their posts. This dissertation reports on a study to evaluate the feasibility of using Docker to address that problem. Docker is a virtualization solution that enables a developer to encapsulate an operating environment—that could show how to manifest or fix a problem—and transfer that environment to others. Our study is organized in two parts. We conducted a feasibility study to broadly assess willingness and effort required to adopt the technology. We also conducted two user studies to assess how well people works the idea. In summary, our results indicate that Docker is useful the most to support configurationrelated posts of medium and high difficulty, which we found to be an important class of posts. We also noted that interest of the community on a tool we developed to support our experiments was high. We believe that these results provide early evidence indicating that the use of Docker to assist developers in Q&A forums should be encouraged in certain cases.